2015
DOI: 10.1021/acsami.5b08539
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Near-Infrared Fluorescent Organic Nanoparticles with a Large Stokes Shift for Noninvasive Long-Term Cellular Imaging

Abstract: Fluorescent organic nanoparticles based on small molecules have been regarded as promising candidates for bioimaging in recent years. In this study, we report a highly stable near-infrared (NIR) fluorescent organic nanoprobes based on nanoparticles of an anthraquinone derivate with strong aggregation-induced emission (AIE) characteristics and a large Stokes shift (>175 nm). These endow the nanoprobe with high fluorescent brightness and high signal-to-noise ratio. On the other hand, the nanoprobe also shows low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 64 publications
4
99
0
Order By: Relevance
“…Fluorescence 3D construction has been performed using vector analysis with respect to the tumor and detector coordinates, which is utilized for the calculation of tumor voxel intensities [83]. A recent study by Michele et al has shown the 3D modelling of tumor spheroids for in vitro analysis [84].…”
Section: 3d Tomographymentioning
confidence: 99%
“…Fluorescence 3D construction has been performed using vector analysis with respect to the tumor and detector coordinates, which is utilized for the calculation of tumor voxel intensities [83]. A recent study by Michele et al has shown the 3D modelling of tumor spheroids for in vitro analysis [84].…”
Section: 3d Tomographymentioning
confidence: 99%
“…Small organic molecules can be highly fluorescent, although they may suffer poor solubility in aqueous media (particularly so for red and infrared dyes), limiting their use for bioapplications . Loading an organic dye into a nonfluorescent nanocarrier, arranged as fluorescent organic nanoparticle (FON), offers an interesting strategy to bring organic dyes in aqueous media, since the obtained FONs have in general good brightness, photostability, and biocompatibility . These nanostructures also have well‐known physicochemical properties and can be loaded or grafted with bioactive compounds and/or targeting agents, to produce multifunctional nanoparticles for theranostic applications …”
mentioning
confidence: 99%
“…This system is a good candidate for performing fluorescence imaging of cancer over an extended period of time. 168 …”
Section: Polymer-core and Fluorophore Nanoparticlesmentioning
confidence: 99%